Comparative characteristics of the physico-chemical stability of basalt scales of various modifications in physiological solutions - Boshytska, N. V.; Fedorenko, Ju. A.; Protsenko, L. S.; Budilina, O. N.; Bondar, V. V.; Uvarova, I. V. (Reports of the National Academy of Sciences of Ukraine, 2015)
The article describes the research of the physico-chemical stability of original basalt scale and that processed under special conditions at temperatures of 500, 800, 900 ºC in physiological solutions. It is established that the tested basalt scales of different modifications exhibit the physical and chemical stability in all physiological solutions, except the Ringer–Locke one. Its activation increases the stability of a powder in the Ringer–Locke solution, which grows with the temperature. At a temperature of 900 ºC, the amount of iron in the filtrate was close to 0 (traces). The stability of a crystal modification of basalt scale in biological environments makes it a perspective material as a dispersion-strengthening additive for orthophosphate materials.